Memória social da Batalha do Jenipapo: trilhas e enredos patrimoniais em Campo Maior (PI) - Maria Dione Carvalho de Moraes; Juliana Rodrigues Cavalcante (Ciências Sociais Unisinos)
Today, there is a considerable increase in the field of cultural referents to be "preserved" and, as a consequence, a proliferation of institutions/mechanisms triggered in face of the threat of disruption/disappearance of these referents, with a growing appreciation of local identities and a questioning of the past on the basis of circumstances and needs of the present. Within this memory boom, we focus the process of assigning meanings to an event narrated by historiography and oral tradition as an important fight in the process of Brazil's independence, viz. the battle of Jenipapo, which occurred in the village of Campo Maior (PI), in the northeastern region of Brazil, on the banks of the River Jenipapo on March 13, 1823. To this end, we approach the polyphonic and multiple work of social memory that takes place in the convergences and divergences between history, myth and tangible signs, as diffuse monuments, places of memory, in the city of Campo Maior (PI).